S130 Axl receptor tyrosine kinase on airway macrophages has a key role in lung immune homeostasis. (12th November 2015) - Denny, N; Grabiec, AM; Tavernier, G; Holden, S; Francis, H; Ryan, D; Niven, R; Fowler, SJ; Simpson, A; Hussell, T
Abstract : Rationale: Apoptotic cell uptake (efferocytosis) by airway macrophages (AMs) is critical for lung immune homeostasis and is defective in chronic lung diseases, including asthma, 1 although the molecular mechanism behind this remains unknown. The TAM (Tyro3, Axl, MerTK) receptor tyrosine kinases are one of the main receptor classes that mediate efferocytosis but little is known about their regulation and function in inflammatory lung diseases. Aim: To investigate expression profile of TAM receptors and their ligand Gas6 in human AMs and analyse potential defects in TAM receptor expression in chronic lung inflammation. Methods: AMs from the sputum of patients with asthma (BTS step 3–5) (n = 30) or healthy donors (HD) (n = 12) were enriched by plastic adhesion. Monocytes were isolated from matched whole blood samples by CD14 positive selection and differentiated into monocyte-derived macrophages (MDMs). Total RNA was extracted from all purified cell populations and mRNA expression analysed by qPCR. HD MDMs were stimulated with Th2 cytokines in vitro and TAM receptor expression was analysed using qPCR and ELISA. Main results: Axl was the dominant TAM receptor expressed in HD AMs whereas monocytes and MDMs predominantly expressed MerTK. Axl expression was significantly reduced in AMs from patients with asthma compared to HD (p < 0.0001), while mRNA levels of MerTK and Gas6 was similar in both groups. We found no differences in Axl and MerTK expression in monocytes and MDMs from HD and patients with asthma, indicating that the observed differences were restricted to the site of inflammation. In vitro, MDM stimulation with IL-4 or IL-13 downregulated Axl mRNA and protein expression in a time-dependent manner. Conclusions: We have shown for the first time that Axl is the principal TAM receptor expressed in human AMs. Significant reduction of Axl expression in AMs from patients with asthma might be responsible for inefficient clearance of apoptotic cells from the inflamed airways and contribute to persistent airway inflammation. Strategies aimed at restoration of Axl expression or activity may represent a novel therapeutic strategy in asthma and other chronic lung diseases. Reference: 1 Simpson JL, Gibson PG, Yang IA et al . Impaired macrophage phagocytosis in non-eosinophilic asthma. Clin Exp Allergy . 2013;43 :29–35